2008
DOI: 10.1007/s11606-008-0512-5
|View full text |Cite
|
Sign up to set email alerts
|

Caring and Dominance Affect Participants’ Perceptions and Behaviors During a Virtual Medical Visit

Abstract: BACKGROUND: Physician communication style affects patients' perceptions and behaviors. Two aspects of physician communication style, caring and dominance, are often related in that a high caring physician is usually not dominant and vice versa.OBJECTIVE: This research was aimed at testing the sole or joint impact of physician caring and physician dominance on participant perceptions and behavior during the medical visit. PARTICIPANTS AND DESIGN:In an experimental design, analog patients (APs) (167 university s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…Physician dominance may explain, in part, why patients in this study were passive. 41 Use of decision aids can promote shared decision making, and such aids exist for deciding about PCI for stable angina. 42 However, these decision aids are used infrequently.…”
Section: Discussionmentioning
confidence: 99%
“…Physician dominance may explain, in part, why patients in this study were passive. 41 Use of decision aids can promote shared decision making, and such aids exist for deciding about PCI for stable angina. 42 However, these decision aids are used infrequently.…”
Section: Discussionmentioning
confidence: 99%
“…If the counselor is verbally dominant little room is left for counselees to ask questions and initiate discussions on topics of counselees' interest. Verbal dominance may have led to counselee submissiveness and reduced engagement [49] with heightened anxiety as a consequence. However, a previous study found that counselors provided more information to counselees in higher need for emotional support [24].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of physician-patient communication, physician nonverbal dominance (e.g., talking more, adopting a dominant tone of voice) has been related to lower patient satisfaction (Bertakis, Roter, and Putnam 1991;Burgoon et al 1987;Hall et al 1994), and especially when nonverbal dominance is expressed by female physicians (Schmid Mast, Hall, and Roter 2008).…”
Section: Nonverbal Dominance and Social Interaction Outcomesmentioning
confidence: 99%
“…For instance, nonverbal dominance of the interaction partner affects an individual's own dominance reactions. Two individuals interacting with each other generally achieve contrast in their dominance behaviors: If A behaves in a high dominant way, B is likely to behave in a less dominant way (Sadler et al 2009;Schmid Mast, Hall, and Roter 2008;Tiedens and Fragale 2003). Interactional and situational characteristics must be taken into account as well when studying expressed and perceived verticality.…”
Section: Individual Characteristics Related To Verticalitymentioning
confidence: 99%